A formal approach to building incremental and hierarchical information and logical models - N. Komkov; A. Lazarev (Модернизация, инновация, развитие, 2016)
This article provides a formalized approach to building incremental and hierarchical information and logical models of scientific-technological and socio-economic forecasts. We consider a set of tools for modeling problems: from identification of needs to produce a certain kind of result, the content of which corresponds to the external signs of this condition. Establish the desired future state of the process of characterizing the intended result is equivalent to the formation of development. Procedures for constructing incremental and hierarchical information and logical models can be used in the mode of using dialogue "director - executor", and presented in the form of logical relations and set-theoretic rules harmonizing information components allows for a meaningful level to form simple questions for the artists and executives.